Estimating The Abundance and Composition of Soil Seed Bank at Bekol Savanna in Baluran National Park, West Java - Nurmuliayanti Muis; Titiek Setyawati; Sukisman Tjitrosoedirdjo; Y.M.D. Ratnadewi (Foresty Faculty of Hasanuddin University, 2018)
The composition of soil-seed bank reflects the condition of vegetation in the past and could be used for predicting the composition of plants that will grow in the future. This study aims to determine the amount and composition of soil-seed bank in Bekol savanna, Baluran National Park. Soil samples were taken using a combination method of quadrat-transect on the invaded and not invaded areas by Acacia nilotica. Soil samples were extracted using wet-sieving method. After the extraction process, the seeds were identified and calculated using a stereo microscope. The result showed that soil-seed bank density was lower at the invaded location (7,566.88 seeds/m3) as compared to the uninvaded location (16,798.3 seeds/m3). The soil-seed bank was found in the invaded site comprising 12 species of broadleaved weeds and 5 species of grasses from 7 families, whereas those in the uninvaded area consisted of 10 species of broadleaved weeds and 7 species of grass from 8 families. This study showed that the invasion of A. nilotica significantly affected the amount and composition of soil-seed bank in various soil depths of Bekol savanna.